查看: 1137|回复: 2
|
help me solve pls~~~thx
[复制链接]
|
|
(sin^2 3x)/(sin^2 x) - (cos^2 3x)/(cos^2 x) = 8 cos 2x |
|
|
|
|
|
|
|
发表于 24-7-2010 09:38 PM
|
显示全部楼层
(sin^2 3x)/(sin^2 x) - (cos^2 3x)/(cos^2 x)
=[(sin 3x/sin x)+(cos 3x/cos x)][(sin 3x/sin x)-(cos 3x/cos x)]
={[(2*sin 2x*cos x - sin x)/sin x]+[(2*cos 2x*cos x - cos x)/cos x]}{[(2*sin 2x*cos x - sin x)/sin x]-[(2*cos 2x*cos x - cos x)/cos x]}
={[(4*sin x*cos^2 x - sin x)/sin x]+(2*cos 2x - 1)}{[(4*sin x*cos^2 x - sin x)/sin x]-(2*cos 2x - 1)}
=(4*cos^2 x -1+2*cos 2x -1)(4*cos^2 x -1-2*cos 2x +1)
=(4*cos^2 x+4*cos^2 x -4)(4*cos^2 x-4*cos^2 x +2)
=(8*cos^2 x -4)(2)
=4*2(2*cos^2 x -1)
=8(cos 2x) [Shown]
打到很乱
别介意。。。 |
|
|
|
|
|
|
|
发表于 25-7-2010 12:56 AM
|
显示全部楼层
回复 1# 乖学生
sin² 3x / sin²x - cos² 3x / cos² x
=(sin 3x/sinx)² - (cos 3x/cos x)²
=[(3sinx-4sin³x)/sinx]² - [ (4cos³x-3cosx)/cosx]²
=(3-4sin²x)² - (4cos²x-3)²
=(3-4sin²x+ 4cos²x-3) (3-4sin²x-4cos²x+3) ......... p²-q²=(p+q)(p-q)
=[ 4(cos²x-sin²x)][6-4(cos²x+sin²x)]
=(4 cos2x)(2)
=8 cos 2x |
|
|
|
|
|
|
| |
本周最热论坛帖子
|